ANALISIS KINERJA PRODUKSI DAN STRATEGI PEMASARAN AGROINDUSTRI KERUPUK KEMPLANG DI KOTA BANDAR LAMPUNG - Andy Lareza; Adia Nugraha; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purposes of this study are analyzing the production performance, identifying internal and external environment, and determining the priority of kerupuk kemplang agroindustry marketing strategy.  The location of the study is determined deliberately as the consideration the area is the production center of kerupuk kemplang agroindustry in Bandar Lampung.  The number of respondents are 14 kerupuk kemplang agroindustry owners that are randomly selected disproportionately.  Data were collected in January – February 2020.  The analytical methods used are the analysis of production performance, SWOT (Strenghts, Weakness, Opportunities, Threats) analysis, and QSPM (Quantitative Strategic Planning Matrix) analysis.  The results of the study indicated that kerupuk kemplang agroindustrial performance based on productivity aspect, capacity, quality, and speed of delivery are in good category, while based on the flexible aspects are not in good category.  The main strength of kerupuk kemplang agroindustry is the location of strategic business and close to suppliers.  Main drawback is the location of the business away from some consumers. The main opportunities are the need and high consumer interest on the product.  The main threat is the supply of reduced raw material when approaching holiday seasons.  The strategy of priority is improving the quality of products, following the bazaar organized by the government, utilizing technologies such as e-commerce and social media, collaborating with a kerupuk kemplang agent, and optimizing the utilization of strategic business locations to increase production volumes by improving cooperation with suppliers. Key words: kerupuk kemplang agroindustry, marketing strategies, production performance